Internal Workload of NoSQL Relational Database (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
In this article we present the scheme of internal workload of typical relational database supporting NoSQL human interaction protocol, we state that the production consumption of query complexity cannot be avoided and modern techniques like explain plan play vital role in bringing the functionality of database server to the end-user with support of open data storage like CSV file format which, in turn, is textual – thus, the question of open storage is discussed in this work within the unlimited support of table sheet formats like CSV, as to the modern Big Data trends we propose the solution used supposedly empirically by popular SQL database systems – this is a plan to run the incoming query and transform the result to the format which can be adopted for final output; we also develop the end programmable product using C# programming language and .NET framework which are the modern programming environments for proper development of platform independent software – the proof of important theorems of relational database query complexity processing and optimization is also given.
Keywords: NoSQL; data processing; relational database; open storage